2018
DOI: 10.1111/bjh.15396
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycarbamide adherence and cumulative dose associated with hospital readmission in sickle cell disease: a 6‐year population‐based cohort study

Abstract: Sickle cell disease (SCD) is a congenital haemoglobinopathy that causes frequent acute care/emergency room visits and hospital admissions for affected individuals. Evidence from population-based studies demonstrating the role of hydroxycarbamide (HC, also termed hydroxyurea) in reducing hospital readmission rates is limited. Our objective was to describe the use of HC and its association with acute care utilization and readmission rates using a large, nationally-representative US health insurance claims databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…The key characteristics of 15 included studies are presented in Table 3. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Five retrospective studies evaluated electronic medical records (EMRs) [33][34][35]38,42 and nine studies were retrospective database analyses. [30][31][32]36,37,39,40,43,44 One study used data from the Sickle Cell Data Collection Program, a registry collecting data from Georgia and California.…”
Section: Overview Of Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key characteristics of 15 included studies are presented in Table 3. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Five retrospective studies evaluated electronic medical records (EMRs) [33][34][35]38,42 and nine studies were retrospective database analyses. [30][31][32]36,37,39,40,43,44 One study used data from the Sickle Cell Data Collection Program, a registry collecting data from Georgia and California.…”
Section: Overview Of Search Resultsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Five retrospective studies evaluated electronic medical records (EMRs) [33][34][35]38,42 and nine studies were retrospective database analyses. [30][31][32]36,37,39,40,43,44 One study used data from the Sickle Cell Data Collection Program, a registry collecting data from Georgia and California. 41 Fourteen studies reported on HCRU, 30,[32][33][34][35][36][37][38][39][40][41][42][43][44] while one reported direct medical costs.…”
Section: Overview Of Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative data are often used for population-level assessments of utilization of care or expenditures, especially for conditions with low prevalence. For example, U.S. insurance claims databases, both Medicaid and private insurance, have been used to estimate medical costs, 2,3,32,33 uptake of antibiotic prophylaxis, 19,26,28,31,34,48 documented receipt of immunizations, 31,34,47,57 use of hydroxyurea, 35,37,55,[58][59][60][61][62][63] and receipt of transcranial doppler (TCD) screening among individuals with SCD. 27,31,38,46,47,[64][65][66] Some of those studies, especially ones published in the past 5 years, merged NBS or clinical databases, which were used to identify cases of SCD, with linked claims data that were used to track utilization of services.…”
Section: Discussionmentioning
confidence: 99%
“…Paulukonis et al proposed the combination of an ICD-9-CM code for SCD in at least two healthcare encounters, independent of setting, and at least one code for an associated treatment, procedure, or complication of SCD, 54 an approach recently adapted by other researchers. 55,56 However, Snyder et al reported that algorithm had a false-negative rate (1 minus sensitivity) of 14.2%, compared with 4.0% for one requiring 3 diagnostic claims. 23…”
Section: Combinations Of Diagnosis Codes With Scd-associated Treatmenmentioning
confidence: 99%